Black and white differences in subjective survival expectations: An evaluation of competing mechanisms - Shayna Fae Bernstein; Isaac Sasson (Elsevier, 2023)
While black-white inequality in longevity is well documented in the United States, little is known about how individuals from different race/ethnic groups form their own personal survival expectations. Prior research has found that despite having higher mortality, blacks on average report higher survival expectations relative to whites. Using data from the Health and Retirement Study, we examined racial differences in subjective survival expectations across birth cohorts and provide explanatory mechanisms.We find that blacks-men in particular-were overly optimistic about their survival, but this effect had waned with successive birth cohorts. Furthermore, whereas subjective survival expectations and actual survival were correlated among white men, among black men the most optimistic fared worst. Blacks and whites differed not only in their response patterns, but also in how they weighed the different factors (socioeconomic, psychosocial, health, parental longevity) associated with expected survival. Importantly, those who estimated their survival probability with certainty had positive psychosocial characteristics, irrespective of race, but only whites had better health.These findings underscore the importance of group differences in subjective survival expectations as another potential form of inequality. Racial differences in how long individual expect to live may account for differences in social and economic behavior and outcomes, irrespective of actual longevity differentials.